PBMC-engrafted humanized mice models for evaluating immune-related and anticancer drug delivery systems - Kametani, Yoshie; Ito, Ryoji; Manabe, Yoshiyuki; Kulski, Jerzy K.; Seki, Toshiro; Ishimoto, Hitoshi; Shiina, Takashi (Frontiers in Molecular Biosciences, 2024)
Immune-related drug delivery systems (DDSs) in humanized mouse models are at the forefront of cancer research and serve as bridges between preclinical studies and clinical applications. These systems offer unique platforms for exploring new therapies and understanding their interactions with human cells and the immune system. Here, we focus on a DDS and a peripheral blood mononuclear cell (PBMC)-engrafted humanized mouse model that we recently developed, and consider some of the key components, challenges, and applications to advance these systems towards better cancer treatment on the basis of a better understanding of the immune response. Our DDS is unique and has a dual function, an anticancer effect and a capacity to fine-tune the immune reaction. The PBL-NOG-hIL-4-Tg mouse system is superior to other available humanized mouse systems for the development of such multifunctional DDSs because it supports the rapid reconstruction of an individual donor’s immunity and avoids the onset of graft-versus-host disease.